Estratégias projetuais no território do porto de Santos - Arriagada, Carlos Andrés Hernández (2012)
Having been searching strategies projective for the territory transformation of Port of Santos, this thesis shows the hinterland - zone between lands - as an opportunity of the territorial reconfiguration in Santos, generating greater urbanity and not only port infrastructure. The factors of transformation of the territory are evaluated due to degradation and also considering prospects directed for this territory; this area with high economic potential due to improvement and discovery in 2007 of the salt layer in the Santos basin, provide scenarios defined for future changes. The proposal is the hinterland, located between the town and the water and is used as logistical warehouse of the transfer goods and movement of economic amounts. It is noticeable in this process the role of different agents in local transformations, thus it was possible to consider and compare strategic actions in other global ports, models possibilities of the transformation and territorial integration, the "hub-port's". The strategic actions in economy, governance, sustainability and urbanity are defined as inducing scenarios applied in the port territory, urbanized and pleasant and not only in a territory of logistics infrastructure.